Teaching and assessing intercultural communicative competence : revisited - Byram, Michael (Bristol ; Blue Ridge Summit, PA : Multilingual Matters, 2021)
"This revised edition of Michael Byram's classic 1997 book updates the text in light of both recent research and critiques and commentaries on the 1st edition. The book is an invaluable guide for teachers and curriculum developers, taking them from a definition of Intercultural Communicative Competence through planning for teaching to assessment"--
Includes bibliographical references and index.
Keywords: Language and languages -- Study and teaching; Multicultural education; Intercultural communication -- Study and teaching; Communicative competence